Role of Commercial Banks In Microfinance: Exploring the relationship between commercial banks and microfinance (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Micro finance is avery important tool for financing the poor. The term “microfinance” (MF) refersto the provision of banking services to lower-income people, especially thepoor. In the history of MF, microfinance institutions (MFIs) have been thefirst to identify the large unserved demand for microcredit in developingcountries, develop methodologies for delivering and recovering small loans, andbegin credit programs for the poor. Given their nature, though, MFIs cannormally meet only a fraction of the demand for microloans in their serviceareas. Commercial banks have begun to see MF as a potentially profitablebusiness and are starting to venture into this field. Micro finance activitieshave gained much popularity, now days due to accelerated growth rate of bankingservices. In a narrower sense, micro finance means ‘Banking for the poor.’ Itincludes the provision of extending credit and other financial products andservices to the poor. It includes the provision of extending credit and otherfinancing products and services to the poor people, in small amounts. The paperdeals with the introduction of micro finance and micro financing in India. Thispaper aims at exploring the main aspects related to commercial banks’ provisionof microfinance services and the future prospects for this activity.  This paper helps to analyse the relationshipof commercial banks with microfinance.